1993
DOI: 10.2109/jcersj.101.1315
|View full text |Cite
|
Sign up to set email alerts
|

Superionic Conduction in Rapidly Quenched Li<sub>2</sub>S-SiS<sub>2</sub>-Li<sub>3</sub>PO<sub>4</sub> Glasses

Abstract: Lithium ion conducting glasses were prepared in the system (0.6Li2S•E0.4SiS2)-Li3PO4 by twin-roller rapid quenching. The temperatures of glass transition (Tg) and crystallization (Tc) were determined for the glassy samples with 0-40mol% Li3PO4. The conductivity values at 25•Ž (ƒÐ25) were maximized and the activation energies (Ea) for conduction were minimized at the composition with 5mol% Li3PO4; the maximum ƒÐ25 value was as high as 9•~10-4S•Ecm-1. Since the differ ence between Tg and Tc was also maximized at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 0 publications
1
32
0
1
Order By: Relevance
“…Amounts of H 2 S gas generated from 100 mg of powder samples were measured. A H 2 S gas sensor (GX-2009, Riken Keiki Co., LTD), a fan and a Al 2 O 3 crucible filled with water were placed in a 1750 cm 3 desiccator. The powder samples were placed in the desiccator in air and a desiccator lid was closed.…”
Section: ¹2mentioning
confidence: 99%
See 1 more Smart Citation
“…Amounts of H 2 S gas generated from 100 mg of powder samples were measured. A H 2 S gas sensor (GX-2009, Riken Keiki Co., LTD), a fan and a Al 2 O 3 crucible filled with water were placed in a 1750 cm 3 desiccator. The powder samples were placed in the desiccator in air and a desiccator lid was closed.…”
Section: ¹2mentioning
confidence: 99%
“…27 Li 2 S-SiS 2 based glasses had high conductivities of 10 ¹3 S cm ¹1 at room temperature. 2,3 Li 2 S-P 2 S 5 glasses and glass-ceramics exhibited high conductivities of 10 ¹3 S cm ¹1 at room temperature and wide electrochemical windows of 05 V (vs. Li + /Li). 4,5 Li-Ge-P-S system crystals showed very high conductivities of 10…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the addition of a small amount of Li 4 SiO 4 to the Li 2 S-SiS 2 glasses was reported to improve conductivity and electrochemical stability of the glasses [8][9][10]. 29 Si MAS-NMR spectra of the oxysulfide glasses suggested that a SiOS 3 tetrahedral unit, in which oxygen atom is substituted for sulfur atom in a SiS 4 unit, was produced in the Li 2 S-SiS 2 -Li 4 SiO 4 oxysulfide glasses [10].…”
Section: Introductionmentioning
confidence: 99%
“…A number of lithium ion conducting sulfide and oxysulfide glasses have been prepared by using a rapid meltquenching technique [4][5][6][7][8][9]. We have also developed mechanochemical preparation of sulfide-based glasses from the idea that they are especially favorable for solid electrolytes in application to all-solid-state lithium secondary batteries [10].…”
Section: Introductionmentioning
confidence: 99%